"An orgy of licence?" Democracy and property redistribution in Poland and the Baltics in their international context, 1918–1926. Issue 5 (10th January 2019) - Richter, Klaus
Abstract : The article argues that property redistribution was a major tool of democratization and nationalization in Poland and the Baltics. It provided governments with a means to give peasants a stake in the new democratic states, thus empower the new titular nations and at the same time marginalize former elites, who became national minorities. The most significant acts of property redistribution were the land reforms passed between 1919 and 1925, which achieved the status of founding charters of the new states. Activists of the disenfranchised minorities conceptualized minority protection as the "Magna Carta" of the international order, which should contain the principle of national self-determination and thus safeguard private property, the protection of which was not clearly regulated by international law. By examining the contingencies of the aftermath of the war in East Central Europe as well as discussions about changing conceptions of property ownership in both East Central and Western Europe, the article shows that land reform was meant to counter Bolshevism, but, at the same time, created the impression abroad that the new states themselves displayed revolutionary tendencies and did not respect private property — an image that became a significant argument of interwar territorial revisionists.